An augmented reality workflow for creating 'live' wine labels. (15th March 2023) - Vrigkas, Michalis; Lappas, Georgios; Kleftodimos, Alexandros
Augmented reality (AR) technologies are constantly developing in various fields of communication such as entertainment, education, information, and marketing and other fields such as industrial product design among others. This paper aims to present an integrated AR workflow for the labelling of wine products. The proposed wine label enhancement workflow may work as follows: the wine business comes up with the idea of creating an AR experience for its wine products, and then an AR expert designs the AR experience, and develops the AR application. As a final step in the process, the application is distributed to the users with the use of various platforms and the experience can then be activated by pointing the camera of a mobile device to the bottle label. The AR content is then generated and displayed to the user who can interact with the digital product on a whole new level.